S-band radar wave-absorbing patch and preparation method thereof

The S-band radar wave absorbing patch is prepared by a mixing process of ethylene-propylene rubber and magnetic/carbon composite nanoabsorbent, which solves the problems of poor environmental protection and insufficient performance in the existing technology, and realizes a high-performance and environmentally friendly wave absorbing patch.

CN119899467APending Publication Date: 2025-04-29安徽璜峪电磁技术有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510210074.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The preparation process of existing S-band radar wave absorbing patches is poor in environmental protection and performance needs to be improved.

Method used

The mixing process of ethylene-propylene rubber, magnetic/carbon composite nanoabsorbent, anti-aging agent, vulcanizing agent and crosslinking agent is adopted, and the magnetic/carbon composite nanoabsorbent is screened through ball milling and ultrasonic vibration to obtain the magnetic/carbon composite nanoabsorbent, and the wave absorbing patch is prepared through kneading and vulcanization treatment.

Benefits of technology

The prepared wave absorbing patch has good mechanical properties and excellent wave absorbing properties. It is an environmentally friendly wave absorbing patch that can meet the requirements of current S-band wave absorbing materials, and has the advantages of good mechanical properties, high and low temperature resistance, thin thickness, flame retardant and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899467A_ABST
    Figure CN119899467A_ABST
Patent Text Reader

Abstract

The invention discloses an S-band radar wave-absorbing patch and a preparation method thereof, and relates to the technical field of wave-absorbing materials. Comprising the following steps: S1, mixing ethylene propylene rubber, a magnetic / carbon composite nano absorbent, an anti-aging agent, a vulcanizing agent and a cross-linking agent; s2, mixing to obtain a raw rubber material; s3, carrying out vulcanization treatment on the raw rubber material to prepare a wave-absorbing patch; wherein the magnetic / carbon composite nano absorbent is prepared from carbonyl iron and graphene, and the mass ratio of the carbonyl iron to the graphene is (98.8 to 99.8) to (0.2 to 1.2). The wave-absorbing patch has excellent wave-absorbing performance, has the advantages of being good in mechanical property, resistant to high and low temperature, thin in thickness, resistant to flame and environmentally friendly, and can well meet the requirements of current S-band wave-absorbing materials; due to the combination of carbonyl iron and graphene, the wave-absorbing patch has good wave-absorbing performance in a wide frequency range, and is suitable for various application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of absorbing materials, and in particular to an S-band radar absorbing patch and a preparation method thereof. Background Art

[0002] With the continuous progress of science and technology, electronic and electrical equipment have been developed for a long time, bringing great convenience to people's work and life. At the same time, the radiation and interference generated by electronic and electrical equipment at work will affect people's lives. The increasingly deteriorating electromagnetic environment not only affects communication but also poses a threat to health. Therefore, the research on absorbing materials has attracted much attention. There are more and more applications in military, industrial and civilian fields.

[0003] The polymer-based absorbing patches on the market are mainly obtained by vulcanization molding. After vulcanization, they have a strong odor and are polluting. Increasing the filling amount and thickness can help improve the performance, but it is also subject to certain limitations.

[0004] Although stealth detection has a tendency to develop towards low-frequency and long-wave, the S-band also has a unique role in anti-stealth, so developed countries have deployed S-band phased array radars in their ground-based defense systems. Its wavelength is moderate, and it can utilize the resonant scattering characteristics of the target to a certain extent, and has a good detection effect on some targets that use traditional stealth technology. It can be used as an important part of the anti-stealth detection system, complementing the low-frequency and long-wave radars to improve the comprehensive detection capability of stealth targets.

[0005] After searching, the application scheme of Chinese patent application number CN201710983625.8 discloses an absorbing patch matched with high-silicon / phenolic heat-proof material and its preparation method. The absorbing patch, by weight, its raw materials are composed of nitrile rubber: carbonyl iron powder: iron-silicon-aluminum alloy powder: antioxidant: coupling agent: double two-five vulcanizer: cross-linking aid = 100: (276.0-386.5): (55.2-165.6): 1: 4.4: 3: 2; and is prepared by hot vulcanization molding process. The preparation method in the above patent has the following shortcomings: the preparation process is poor in environmental protection and the performance needs to be improved. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an S-band radar absorbing patch and a preparation method thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing an S-band radar absorbing patch comprises the following steps:

[0009] S1: mixing EPDM rubber, magnetic / carbon composite nano absorbent, antioxidant, vulcanizing agent and cross-linking agent;

[0010] S2: Mixing to obtain a raw rubber material;

[0011] S3: vulcanizing the raw rubber material to obtain an absorbing patch;

[0012] Wherein, the magnetic / carbon composite nano absorber comprises carbonyl iron and graphene, and the mass ratio of the carbonyl iron to the graphene is (98.8-99.8): (0.2-1.2);

[0013] The chemical composition of the carbonyl iron is: Fe≥98.%, N≤0.8%, C≤0.8%, O≤0.4%; the long diameter of the sheet is 3-7 μm (D50); the tap density is 2.20-2.35 g / cm 3 The chemical composition of the graphene is: C>95.0%, sheet length: 1-10 μm (D50), tap density: 0.08-0.10 g / cm 3 , powder resistivity <0.03Ω.㎝.

[0014] Preferably, the preparation method of the magnetic / carbon composite nano absorber is: carbonyl iron and graphene are mixed in a mass ratio of (98.8-99.8): (0.2-1.2) by ball milling to obtain the magnetic / carbon composite nano absorber.

[0015] Preferably, the preparation method of the magnetic / carbon composite nano absorber is as follows: carbonyl iron and graphene are mixed in a mass ratio of (98.8-99.8): (0.2-1.2), and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time is 5-10 hours to obtain ball mill material; and the ball mill material is sieved through a 200-300 mesh ultrasonic vibration sieve to obtain a magnetic / carbon composite nano absorber.

[0016] Preferably: in S1, the step of mixing EPDM rubber, magnetic / carbon composite nano absorber, antioxidant, vulcanizer and crosslinking agent comprises: mixing 90 to 110 parts of EPDM rubber, 300 to 1200 parts of magnetic / carbon composite nano absorber, 0.5 to 2 parts of antioxidant, 1 to 5 parts of vulcanizer and 1 to 3 parts of crosslinking agent by mass.

[0017] Preferably: in S2, the mixing step is: mixing the EPDM rubber, the magnetic / carbon composite nano absorber, the antioxidant, and the vulcanizer, placing them in a plasticator for mixing for 10 min to 20 min, adding the cross-linking agent, mixing for another 5 min to 10 min, and cooling at room temperature for 20 to 30 hours to obtain a raw rubber material.

[0018] Preferably, the mixing method includes one or more combinations of triangle packing, pillow packing, thin-through mixing, and oblique knife mixing.

[0019] Preferably, in S3, the step of preparing the absorbing patch specifically comprises: adding the rubber mixture into a mold of a flat-plate vulcanizer, the operating temperature of the flat-plate vulcanizer is 150 to 180 degrees Celsius, and pressing the rubber mixture into shape for 5 to 15 minutes to prepare the absorbing patch.

[0020] Preferably: the EPDM rubber is EPDM; the antioxidant is N-isopropyl-N'-phenyl-p-phenylenediamine; the vulcanizing agent is 2,5-dimethyl-2,5-bishexane; and the crosslinking agent is triallyl isocyanurate.

[0021] Preferably, the magnetic mixed absorbent is carbonyl iron and graphene in a mass ratio of (98.8-99.8):(0.2-1.2); the graphene is a single-layer hexagonal honeycomb lattice graphene.

[0022] An S-band radar absorbing patch, wherein the absorbing patch is prepared by the above-mentioned preparation method.

[0023] The beneficial effects of the present invention are:

[0024] 1. The absorbing patch of the present invention has good mechanical properties and excellent absorbing properties. It is an environmentally friendly absorbing patch that can well meet the requirements of current S-band absorbing materials. It also has the advantages of good mechanical properties, high and low temperature resistance, thin thickness, flame retardancy, and environmental protection.

[0025] 2. Due to the combination of carbonyl iron and graphene, the absorbing patch has good absorbing performance in a wide frequency range and is suitable for a variety of application scenarios; EPDM rubber is used as the base material, so that the absorbing patch has a light weight and high strength, and has good corrosion resistance, which is convenient for application in various equipment and platforms. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the reflection loss diagram of the absorber with a filling ratio of 85% (99.7% carbonyl iron + 0.3% graphene, thickness 1.00mm);

[0027] Figure 2 This is the reflection loss diagram of the absorber with a filling ratio of 85% (99.7% carbonyl iron + 0.3% graphene, thickness 1.20mm);

[0028] Figure 3 This is the reflection loss diagram of the absorber with a filling ratio of 83% (99.7% carbonyl iron + 0.3% graphene, thickness 1.20mm);

[0029] Figure 4This is the reflection loss diagram of the absorber with a filling ratio of 84% (99.7% carbonyl iron + 0.3% graphene, thickness 1.00mm);

[0030] Figure 5 This is the reflection loss diagram of the absorber with a filling ratio of 80% (99.7% carbonyl iron + 0.3% graphene, thickness 1.20mm);

[0031] Figure 6 This is the reflection loss diagram of the absorber with a filling ratio of 75% (99.7% carbonyl iron + 0.3% graphene, thickness 1.00mm). DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.

[0033] A method for preparing an S-band radar absorbing patch comprises the following steps:

[0034] Carbonyl iron and graphene are mixed in a mass ratio of (98.8-99.8):(0.2-1.2), and put into a bedroom ball mill in a ratio of material: steel ball=1:8, and the ball milling time is 5-10 hours to obtain a ball mill material;

[0035] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0036] The ethylene-propylene rubber, the magnetic / carbon composite nano absorber, the antioxidant and the vulcanizing agent are mixed, the cross-linking agent is added and mixed, and the mixture is cooled at room temperature to obtain a raw rubber material;

[0037] 90-110 parts of the ethylene-propylene rubber, 300-1200 parts of the magnetic / carbon composite nano absorber, 0.5-2 parts of the antioxidant, and 1-5 parts of the vulcanizer are mixed by weight, placed in a double-roller open plasticizer, and after being triangularly packaged or pillow-packaged for 6-10 times, thinned for 5-6 times, mixed for 10-20 minutes, 1-3 parts of a cross-linking agent are added, and then mixed for 5-10 minutes, the sheet is removed, and then cooled at room temperature for 20-30 hours to obtain a raw rubber material; wherein the ethylene-propylene rubber is selected from ethylene-propylene-diene rubber; the magnetic / carbon composite nano absorber powder is selected from carbonyl iron and graphene in a mass ratio of (98.8-99.8): (0.2-1.2); the antioxidant is selected from N-isopropyl-N'-phenyl-p-phenylenediamine; the vulcanizer is selected from 2,5-dimethyl-2,5-bis-hexane; and the cross-linking agent is selected from triallyl isocyanurate;

[0038] The absorbing patch is obtained by hot-pressing the mixed rubber through a mold; specifically, the mixed rubber is added into a mold of a flat vulcanizer, and the mixed rubber is pressed into shape to obtain the absorbing patch, wherein the operating temperature of the flat vulcanizer is 150 to 180 degrees Celsius, and the time is 5 minutes to 15 minutes.

[0039] Embodiment 1:

[0040] Carbonyl iron and graphene were mixed in a mass ratio of 99.7:0.3, and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time was 6 hours to obtain a ball mill material;

[0041] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0042] Mix 100 parts of EPDM rubber, 1 part of N-isopropyl-N'-phenyl-p-phenylenediamine, 600.6 parts of magnetic composite powder, and 3 parts of 2,5-dimethyl-2,5-bishexane by mass;

[0043] Then put it in a double-roller open plastic mill, make a triangle bag 8 times, thin it 6 times, mix it for 15 minutes, add 2 parts of cross-linking agent triallyl isocyanurate, mix it for another 10 minutes and then cut it into sheets;

[0044] Then it was cooled at room temperature for 25 hours to obtain a mixed raw rubber material, and then the mixed raw rubber material was placed on a flat vulcanizer at a temperature of 160° C. and subjected to compression vulcanization molding for 13 minutes to obtain an absorbing patch with a thickness of 1.00 mm.

[0045] Embodiment 2:

[0046] Carbonyl iron and graphene were mixed in a mass ratio of 99.7:0.3, and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time was 6 hours to obtain a ball mill material;

[0047] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0048] Mix 100 parts of EPDM rubber, 1 part of N-isopropyl-N'-phenyl-p-phenylenediamine, 600.6 parts of magnetic composite powder, and 3 parts of 2,5-dimethyl-2,5-bishexane by mass;

[0049] Then put it in a double-roller open plastic mill, make a triangle bag 8 times, thin it 6 times, mix it for 15 minutes, add 2 parts of cross-linking agent triallyl isocyanurate, mix it for another 10 minutes and then cut it into sheets;

[0050] Then the mixture was cooled at room temperature for 25 hours to obtain a mixed raw rubber material, and then the mixed raw rubber material was placed on a flat vulcanizer at a temperature of 160° C. and subjected to compression vulcanization molding for 13 minutes to obtain an absorbing patch with a thickness of 1.20 mm.

[0051] Embodiment 3:

[0052] Carbonyl iron and graphene were mixed in a mass ratio of 99.7:0.3, and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time was 6 hours to obtain a ball mill material;

[0053] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0054] Mix 100 parts of EPDM rubber, 1 part of N-isopropyl-N'-phenyl-p-phenylenediamine, 516.5 parts of magnetic composite powder, and 3 parts of 2,5-dimethyl-2,5-bishexane by mass;

[0055] Then put it in a double-roller open plastic mill, make a triangle bag 8 times, thin it 6 times, mix it for 15 minutes, add 2 parts of cross-linking agent triallyl isocyanurate, mix it for another 10 minutes and then cut it into sheets;

[0056] Then, the mixture was cooled at room temperature for 25 hours to obtain a mixed raw rubber material, and then the mixed raw rubber material was placed on a flat vulcanizer at a temperature of 160°C and subjected to compression vulcanization molding for 13 minutes to obtain an absorbing patch with a thickness of 1.20 mm.

[0057] Embodiment 4:

[0058] Carbonyl iron and graphene were mixed in a mass ratio of 99.7:0.3, and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time was 6 hours to obtain a ball mill material;

[0059] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0060] Mix 100 parts of EPDM rubber, 1 part of N-isopropyl-N'-phenyl-p-phenylenediamine, 556.5 parts of magnetic composite powder, and 3 parts of 2,5-dimethyl-2,5-bishexane by mass;

[0061] Then put it in a double-roller open plastic mill, make a triangle bag 8 times, thin it 6 times, mix it for 15 minutes, add 2 parts of cross-linking agent triallyl isocyanurate, mix it for another 10 minutes and then cut it into sheets;

[0062] Then, the mixture was cooled at room temperature for 25 hours to obtain a mixed raw rubber material, and then the mixed raw rubber material was placed on a flat vulcanizer at a temperature of 160°C and subjected to compression vulcanization molding for 13 minutes to obtain an absorbing patch with a thickness of 1.00 mm;

[0063] Comparative Example 1:

[0064] Carbonyl iron and graphene were mixed in a mass ratio of 99.7:0.3, and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time was 6 hours to obtain a ball mill material;

[0065] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0066] Mix 100 parts of EPDM rubber, 1 part of N-isopropyl-N'-phenyl-p-phenylenediamine, 424 parts of magnetic composite powder, and 3 parts of 2,5-dimethyl-2,5-dihexane by mass;

[0067] Then put it in a double-roller open plastic mill, make triangle bags 8 times, thin through 6 times, mix for 15 minutes, add 2 parts of cross-linking agent triallyl isocyanurate, mix for another 10 minutes, then take out the sheet, and then cool at room temperature for 25 hours to obtain a mixed raw rubber material;

[0068] The mixed raw rubber was then placed on a flat vulcanizer at a temperature of 160°C and subjected to compression vulcanization for 13 minutes to obtain an absorbing patch with a thickness of 1.20 mm.

[0069] Comparative Example 2:

[0070] Carbonyl iron and graphene were mixed in a mass ratio of 99.7:0.3, and put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time was 6 hours to obtain a ball mill material;

[0071] Screening with an ultrasonic vibration sieve of 200-300 meshes to obtain a magnetic / carbon composite nano absorbent;

[0072] Mix 100 parts of EPDM rubber, 1 part of N-isopropyl-N'-phenyl-p-phenylenediamine, 318 parts of magnetic composite powder, and 3 parts of 2,5-dimethyl-2,5-dihexane by mass;

[0073] Then put it in a double-roller open plastic mill, make a triangle bag 8 times, thin it 6 times, mix it for 15 minutes, add 2 parts of cross-linking agent triallyl isocyanurate, mix it for another 10 minutes and then cut it into sheets;

[0074] Then it was cooled at room temperature for 25 hours to obtain a mixed raw rubber material, and then the mixed raw rubber material was placed on a flat vulcanizer at a temperature of 160° C. and subjected to compression vulcanization molding for 13 minutes to obtain an absorbing patch with a thickness of 1.00 mm.

[0075] The absorbing performance of the absorbing patches prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2 was tested respectively. The relationship between reflectivity and frequency is shown in the figure. The measurement results are shown in the following table:

[0076]

[0077]

[0078] The invention provides a method for preparing an absorbing patch, wherein carbonyl iron and graphene are mixed according to a mass ratio by ball milling to obtain a magnetic / carbon composite nano absorber. Ethylene propylene rubber, a magnetic / carbon composite nano absorber, an antioxidant, a vulcanizing agent and a crosslinking agent are mixed, kneaded and vulcanized to obtain an absorbing patch. The absorbing patch of the invention has good mechanical properties and excellent absorbing properties, is an environmentally friendly absorbing patch, and can well meet the requirements of current S-band absorbing materials.

[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an S-band radar absorbing patch, characterized in that: The steps include: S1: mixing EPDM rubber, magnetic / carbon composite nano absorbent, antioxidant, vulcanizing agent and cross-linking agent; S2: Mixing to obtain a raw rubber material; S3: vulcanizing the raw rubber material to obtain an absorbing patch; Wherein, the magnetic / carbon composite nano absorber comprises carbonyl iron and graphene, and the mass ratio of the carbonyl iron to the graphene is (98.8-99.8): (0.2-1.2); The chemical composition of the carbonyl iron is: Fe≥98.%, N≤0.8%, C≤0.8%, O≤0.4%; the long diameter of the sheet is 3-7 μm (D50); the tap density is 2.20-2.35 g / cm 3 The chemical composition of the graphene is: C>95.0%, sheet length: 1-10 μm (D50), tap density: 0.08-0.10 g / cm 3 , powder resistivity <0.03Ω.㎝.

2. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: The preparation method of the magnetic / carbon composite nano absorber is as follows: carbonyl iron and graphene are mixed in a mass ratio of (98.8-99.8): (0.2-1.2) by ball milling to obtain the magnetic / carbon composite nano absorber.

3. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: The preparation method of the magnetic / carbon composite nano absorber is as follows: carbonyl iron and graphene are mixed in a mass ratio of (98.8-99.8): (0.2-1.2), and the mixture is put into a bedroom ball mill in a ratio of material: steel ball = 1:8, and the ball milling time is 5-10 hours to obtain ball milled material; and the mixture is sieved through a 200-300 mesh ultrasonic vibration sieve to obtain the magnetic / carbon composite nano absorber.

4. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: In S1, the step of mixing EPDM rubber, magnetic / carbon composite nano absorber, antioxidant, vulcanizer and crosslinking agent comprises: mixing 90 to 110 parts of EPDM rubber, 300 to 1200 parts of magnetic / carbon composite nano absorber, 0.5 to 2 parts of antioxidant, 1 to 5 parts of vulcanizer and 1 to 3 parts of crosslinking agent in parts by mass.

5. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: In S2, the mixing step is: mixing the EPDM rubber, the magnetic / carbon composite nano absorber, the antioxidant, and the vulcanizer, placing them in a plasticator for mixing for 10 to 20 minutes, adding the cross-linking agent, mixing for another 5 to 10 minutes, and cooling them at room temperature for 20 to 30 hours to obtain a raw rubber material.

6. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: The mixing method includes one or more combinations of triangle packing, pillow packing, thin-through mixing, and oblique knife mixing.

7. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: In S3, the step of preparing the absorbing patch specifically includes: adding the rubber mixture into a mold of a flat-plate vulcanizer, the operating temperature of the flat-plate vulcanizer is 150 to 180 degrees Celsius, and pressing the rubber mixture into shape for 5 to 15 minutes to prepare the absorbing patch.

8. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: The EPDM rubber is EPDM; the antioxidant is N-isopropyl-N'-phenyl-p-phenylenediamine; the vulcanizing agent is 2,5-dimethyl-2,5-bishexane; and the crosslinking agent is triallyl isocyanurate.

9. The method for preparing an S-band radar absorbing patch according to claim 1, characterized in that: The magnetic mixed absorbent is carbonyl iron and graphene in a mass ratio of (98.8-99.8):(0.2-1.2); the graphene is single-layer hexagonal honeycomb lattice graphene.

10. An S-band radar absorbing patch, characterized in that: The absorbing patch is prepared according to the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • A microwave absorbing patch compatible with high-silica / phenolic heat-resistant materials and its preparation method

    CN107652495B